2020
DOI: 10.3390/plants9080958
|View full text |Cite
|
Sign up to set email alerts
|

So Uncommon and so Singular, but Underexplored: An Updated Overview on Ethnobotanical Uses, Biological Properties and Phytoconstituents of Sardinian Endemic Plants

Abstract: The last decades have recorded an increase of plant-based drug discovery processes. Indeed, natural products possess a superior chemical diversity as compared to synthetic ones, leading to a renewal in searching for new therapeutic agents from the plant kingdom. In particular, since the structural variety of natural compounds reflects the biodiversity of their source organisms, regions of the world with high biodiversity and endemism deserve particular interest. In this context, Sardinia Island (Italy), with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 235 publications
(282 reference statements)
0
16
0
Order By: Relevance
“…Cinnamomum [60]; Cinnamomum camphora (L.) [45]; Cistus monspeliensis L. [61]; Cistus salviifolius L. [61]; Cytinus hypocistis (L.) L. [62]; Limonium morisianum Arrigoni [63]; Myrtus communis L. [64]; Origanum vulgare L. [65]; Pistacia lentiscus L. [66]; Pistacia terebinthus L. [67]; Rosmarinus officinalis L. [68]; Salvia officinalis L. [69]; Thymus herba-barona Loise L. [70]; Thymus vulgaris L. [71]; Inula crithmoides [72];…”
Section: Bacterium (Gram+) Number Of Plant Species Plant Namementioning
confidence: 99%
“…Cinnamomum [60]; Cinnamomum camphora (L.) [45]; Cistus monspeliensis L. [61]; Cistus salviifolius L. [61]; Cytinus hypocistis (L.) L. [62]; Limonium morisianum Arrigoni [63]; Myrtus communis L. [64]; Origanum vulgare L. [65]; Pistacia lentiscus L. [66]; Pistacia terebinthus L. [67]; Rosmarinus officinalis L. [68]; Salvia officinalis L. [69]; Thymus herba-barona Loise L. [70]; Thymus vulgaris L. [71]; Inula crithmoides [72];…”
Section: Bacterium (Gram+) Number Of Plant Species Plant Namementioning
confidence: 99%
“…12% are endemic of the Sardinian–Corsican biogeographic province [ 18 ], it represents one of the Mediterranean biodiversity hotspots [ 19 , 20 , 21 ]. This endemic richness is attributable to the long geological history and geographical isolation, in addition to the high geomorphological diversity [ 21 , 22 , 23 ], and it could represent a great source of phytoconstituents, often unique and structurally diverse, due to adaptation to the local environment [ 24 ]. Out of Sardinian Teucrium taxa, the following eight native and spontaneous taxa were selected in this study: T. capitatum L. subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Scrophularia trifoliata L. is an endemic plant of Sardinia, which is known to be used in traditional medical practices of the island for the treatment of different diseases, such as skin disorders and rheumatism [ 16 ]. Despite these traditional uses, to the best of our knowledge, to date only one phytochemical study on S. trifoliata has been reported [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings motivated the investigation of S. trifoliata , based on two interesting considerations. Despite its acceptance and documented uses as antinflammatory, antirheumatic, diuretic, vulnerary, and anthelmintic among Sardinian inhabitants, it is a species underexplored [ 16 ], indeed, only one phytochemical study has been reported until now [ 17 ]. However, overall S. trifoliata is a plant of endemic Sardinian flora and some of Sardinian endemism have shown peculiar specialized metabolites patterns [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation